Innovative waste management technologies for sustainable development - Bhat, Rouf Ahmad 1983-; Qadri, Humaira; Wani, Khursheed Ahmad; Dar, Gowhar Hamid (IGI Global, 2019)
"This book examines new waste management technologies for the control of air, water and soil pollution. It also provides insight on various modern innovative concepts of waste-to-energy and its application in environmental safeguards"--